Device Localization Using mmWave Ranging with Sub-6-Assisted Angle of Arrival Estimation - Maletic, Nebojsa; Sark, Vladica; Gutierrez, Jesus; Grass, Eckhard (2018 IEEE International Symposium on Broadband Multimedia Systems and Broadcasting (BMSB), 2018)
Millimeter wave (mmWave) communication is a promising solution for achieving high data rates and low latency in future wireless networks. 5G systems are expected to fulfill these strict requirements using, among others, mm Waves. The nature of the communication in these bands considering human mobility make the challenges even complex for reasons like high beam training overhead. Features like ranging and localization are becoming key to overcome these limitations. In this paper, we address the problem of device localization in the mm Wave band. We propose a solution that leverages the co-existence of Sub-6 GHz and mmWave connectivity at access and mobile nodes. Our solution relies on Angle of Arrival estimation using Sub-6 signal at the access node. This information is provided to the mmWave part for subsequent beam training phase and high- resolution ranging. To validate the proposed solution, a number of measurements are performed showing its feasibility.